(untitled) (International Journal of Engineering and Computer Science, 2014)
The objective of this work is the study of adsorption of dye solution which is a dye malachite green using corn cob. Removal of this dye from aqueous solution using corn cob has been investigated. Liquid phase adsorption experiments were conducted. Batch adsorption studies are Carried out by observing the effect of experimental parameters, namely, pH, and amount of adsorbents, contact time and initial concentration. Optimum conditions for dye removal are studied like pH value, contact time required, amount of adsorbent, initial concentration, etc. The results generated by this work can be used for determination of optimum conditions for adsorption of dye in aqueous solutions. Dye is present in mixture form in various Industrial effluents like Textile Industries, Sewage water, Water treatment plants. This work can have use in Design of adsorption columns for dyes removal